ZONA KESESUAIAN LAHAN RAWA PASANG SURUT BERBASIS KEUNGGULAN KOMPETITIF KOMODITAS - Yanti Rina D; Haris Syahbuddin (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2013)
The research was aimed to engineer the agriculture development model in KTM  tidal  swampland  that  based  on  resources  utilization  optimizing  (land,  human,and  material),  agriculture  technology  amelioration  and  farm  zoning  based  on competitive  advantage.   The  research  was  conducted  in  Cahaya  Baru  KTM,  Barito Kuala  Regency,  South  Kalimantan  whose  land  was  tidal  swampland.  Data  were collected  by  interviewing  160  respondents  that  had  been  chosen  by  the  mean  of purposive  random  sampling.   Data  was  analyzed  by  using  competitive  advantage method. Research result showed that on tabukan (down part of surjan), for potential field tipology    with A, B and C overflow type on wet rice field (surjan available)  was afforded by using cropping pattern with new paddies variety. that turn to be more competitive  than  local  paddy  variety  plant.  Whereas,  on  A  and  B  sulfate  acid  tidal swampland  would be more profitable if were afforded with new paddies  variety and C overflow    type was afforded with local paddy  variety. Vegetable plant above guludan (raise bed) on sulfate acid field typology and potential for  A and B  overflow typology were  using cropping pattern of chili (MH)-  tomato (MKI)-tomato (MKII) which most competitive.  Whereas,  for C  type  of  overflow  typology  the  cropping  pattern  of  chili (MH)  –  tomato (MK I) was the most competitive. These competitive  advantage  were visualized on commodities competitive advantage map on 1 : 55.000 scale.